Optimizing hemostasis in thoracic surgery: a systematic review and meta-analysis of perioperative antifibrinolytic therapy - Muhammad Hamza; Zohad Shah; Hasnain Wajeeh Saqib; Syeda Rabiah Shahid; Muhammad Murad Khurshid; Sheza Irfan; Aizaz Anwar Khalid; Arshdeep Singh; Ikram Ul Haq Chaudhry; Asif Raza Shah (The Cardiothoracic Surgeon, 2026)
Abstract Background Excessive perioperative bleeding remains a major challenge in non-cardiac thoracic surgeries. Antifibrinolytic therapy can enhance hemostasis and reduce transfusion requirements, although its use carries a theoretical risk of postoperative thromboembolic complications that warrants evaluation alongside its hemostatic benefits. Main text Methods: For this systematic review and meta-analysis, we searched multiple databases for studies that compared antifibrinolytic therapy with placebo or no intervention in adult patients undergoing non-cardiac thoracic surgery. Primary outcomes included intraoperative and early postoperative bleeding and blood transfusion requirements. Additionally, thromboembolic events, length of hospital and ICU stay, respiratory complications, and all-cause postoperative mortality were also analyzed. Standardized mean differences (SMDs), mean differences (MDs), or odds ratios (ORs) with 95% confidence intervals (CIs) were used for pooled estimates, while the I² statistic was used to assess heterogeneity. Results Fifteen studies were included. Antifibrinolytics significantly reduced postoperative 24-hour (SMD − 1.04, 95% CI − 1.64 to − 0.43) and 12-hour (SMD − 1.06, 95% CI − 2.22 to 0.10) blood loss, intraoperative blood loss (SMD − 0.48, 95% CI − 1.05 to 0.08), total RBC transfusion (SMD − 0.54, 95% CI − 0.80 to − 0.28) and duration of hospital stay (MD − 0.96 days, 95% CI − 1.84 to − 0.08). IV route reduced 24-hour blood loss same topical, and aprotinin shortened hospital stay. Sensitivity analyses confirmed robustness, while meta regression identified publication year as a key moderator, explaining 19% of variance. No significant differences were observed for ICU stay, hemoglobin levels, thromboembolic events, respiratory complications, or mortality. Conclusions Perioperative antifibrinolytic therapy in non-cardiac thoracic surgery improves hemostatic control, reduces transfusion requirements, and shortens hospitalization, with no significant increase in thromboembolic, respiratory, or mortality outcomes observed; however, these safety analyses were based on a limited number of studies and should be interpreted with caution.